Stress at workplace and how to manage it’s effectively among employees in Dungun banking sectors / Noorazeilah Abd Manaf - Abd Manaf, Noorazeilah (2013)
This study investigated the factors of stress at the workplace and how to manage it’s effectiveness. As everyone noticed, stress was an unavoidable phenomenon in every aspect of human life. It was generally an emotional imbalance which may be due to several reasons such as the content of the work, socio-economy factors and also the health lifestyle factors. Stress at the workplace has also become common in today's organization. In order to recognize the stress at the workplace, there are few factors should be considered. The scope of study emphasized the significant relationship between independent variables (the content of the work, socio-economy and health lifestyle factor) among employees in Dungun banking sectors. This research is focusing on employees in Dungun banking sectors. This study used the stratified sampling and highlights 168 respondents. For this study, sets of questionnaires were distributed to the respondents. The questionnaires consist of 5 sections which are A, B, C, D and E sections. 4 sections come from variables sections and 1 section come from demographic profile sections. Using personally administered questionnaires with bilingual language of English and Malay language. The data collected were analyzed by using the computer software known as Statistical Package for Social Science (SPSS) version 20.0 and were analyzed by using several tests. Statistical analysis such as reliability analysis, frequency analysis, Pearson correlation analysis, descriptive analysis and multiple regression analysis were used. The findings indicated that the majority of the respondents have a level of stress ranging from moderate to strong, with the most stressful factor which is the content of the work. The result of this study may contribute to the development and performance of strategies to promote the effective stress management among the employees. Thus, based on the findings, recommendations for team management are discussed and further research is suggested.